MENGEMBANGAN POTENSI ANAK USIA DINI MELALUI BUDAYA SUNDA - Nina Kurniasih; Almadina Rakhmaniar; Robby Rachman (Jurnal Penelitian Sosial Ilmu Komunikasi, 2021)
The development of children's potential in Early Childhood Education (PAUD) in the era of globalization is currently facing big challenges. In especial, the challenge of the entry of global culture or foreign culture into Indonesia that is not in accordance with the value system and culture of the Indonesian nation which carries full value, norms, customary ethics and local culture as well as other values and principles, This causes an impact on Indonesian education and culture and is feared that it will erode and threaten the existence of Sundanese culture as a local cultural part of the Indonesian nation's culture, in order to always exist and be strong, we need a way to maintain it. One of the solution is by synergize and integrating Sundanese culture in early childhood education, which is considered the Golden Age, a phase that determines the future of children. is through Sundanese culture in the form of Sundanese cultural philosophies or values and pupuh, is hoped that in addition to being able to be a way to conserve the local wisdom of Sundanese culture and as a filter from the negative impact of foreign cultures, it can also develop the potential of early childhood. other than that the opinion of experts also shows that the values and philosophies contained in Sundanese culture are in accordance with the principles of the national educational goals.